The Effects of Quality of Technology on Learning Performance in Remote Lectures - Himmanen, Joonas (2025)
After the events of the past few years, universities have continued to appreciate the concept of hybrid and most lectures are still accommodating remote participation. However, while the situation has improved from the early 2020, both students and lecturers are still facing numerous technology related issues, common complaints being the quality of audio, video and a general lack of understanding of the technology. In this thesis, I am examining these issues and identifying solutions in order to make recommendations to educational institutions on how to ensure that the quality of technology does not come in the way of students’ learning performance.